Chemical characteristics of soybean meal milk residue, obtained from soybean meal and full-fat soy flour - Júnior, Vitorino Martinelli; Andrade, Pedro de; Andrade, Antonio Tadeu de; Rosa, Luiz Claudio de A.; Sampaio, Alexandre Amstalden M.; Oliveira, Mauro Dal Secco de (Pesquisa Agropecuaria Brasileira, 2014)
This work was conducted with the objective of studying the effects of different periods of time (two, four and six hours) and temperature (50°C, 65°C and 80°C), substrate full-fat soy flour and soybean meal in soybean milk residue. To obtain the residue, a stainless steel machine was used, with a thermostat for temperature control and constant agitation. The model for statistical analysis was in factorial 3 x 3 x 2 with two replications. It was concluded that the treatments didn’t present marked differences in the chemical and mineral composition of the residue. The protein content of the meal’s residue are slightly high to the content of the meal from residue originated. The ether extract content of the full-fat soy flour residue was similar to full-fat soy flour (21.41%) and soybean meal residue were lightly lower.